(untitled) (International Journal of Industrial Engineering and Construction Management (IJIECM), 2026)
The integration of artificial intelligence (AI) in construction management has ushered in transformative advancements in safety protocols, reshaping traditional practices with innovative, data-driven methodologies. This paper examines the deployment of AI technologies to enhance safety measures, aiming to mitigate risks inherent in construction environments. AI-driven systems, leveraging machine learning algorithms and computer vision, provide real-time hazard detection and predictive analytics, which foster a proactive approach to safety management. These technologies not only improve incident response times but also contribute to a significant reduction in workplace accidents by identifying potential risks before they manifest. In the context of construction management, AI's capabilities extend to the automation of routine safety checks, enabling the continuous monitoring of compliance with established safety standards. Through the analysis of vast amounts of data generated on construction sites, AI systems can discern patterns and predict potential safety violations, thus allowing managers to implement timely corrective measures. Furthermore, the integration of AI facilitates the optimization of resource allocation, ensuring that safety personnel and equipment are deployed strategically to high-risk areas, thereby enhancing overall site safety. The paper also explores the economic implications of adopting AI-driven safety protocols. While the initial investment in AI technologies may be substantial, the long-term benefits include reduced insurance costs, fewer project delays, and diminished liability risks, which collectively contribute to a more efficient and cost-effective operation. Moreover, the deployment of AI in safety protocols aligns with the broader industry trend towards digital transformation, positioning construction firms at the forefront of technological innovation. In conclusion, this study underscores the critical role of AI in revolutionizing safety management within the construction industry. By adopting AI-driven approaches, construction managers can not only safeguard the well-being of their workforce but also enhance operational efficiency, thereby setting new benchmarks for safety standards in the industry.